English as a Tool of British Political and Linguistic Imperialism in Chinua Achebe’s A Man of the People - Naeema Shah (University of Chitral Journal of Linguistics and Literature, 2019)
The spread of English is considered as a tool of British political and linguistic imperialism in effects of globalization. Kachrus Three Circle model of World Englishes has always played significant role in the categorization of the spread of English. This model is always used as an important tool to critically analyze the distributed circle of English speaking regions in the world where English is dominant over other languages and cultures. In the present study the outer circle from Kachrus model is focused. A Man of the People by Chinua Achebe has been analysed through the lens of Kachrus Three Circle Model of World Englishes. The study finds that the spread of English is basically a tool used for homogenized attack by British imperialism in order to subdue other cultures, politically and linguistically.